A Haptic Sleeve as a Method of Mechanotactile Feedback Restoration for Myoelectric Hand Prosthesis Users - Borkowska, Violet R.; McConnell, Alistair; Vijayakumar, Sethu; Stokes, Adam; Roche, Aidan D. (Frontiers in Rehabilitation Sciences, 2022)
Current myoelectric upper limb prostheses do not restore sensory feedback, impairing fine motor control. Mechanotactile feedback restoration with a haptic sleeve may rectify this problem. This randomised crossover within-participant controlled study aimed to assess a prototype haptic sleeve’s effect on routine grasping tasks performed by eight able-bodied participants. Each participant completed 15 repetitions of the three tasks: Task 1 – normal grasp, Task 2 – strong grasp and Task 3 – weak grasp, using visual, haptic, or combined feedback All data were collected in April 2021 in the Scottish Microelectronics Centre, Edinburgh, UK. Combined feedback correlated with significantly higher grasp success rates compared to the vision alone in Task 1 (p<0.0001), Task 2 (p=0.006) and Task 3 (p=0.0170). Similarly, haptic feedback was associated with significantly higher grasp success rates compared to vision in Task 1 (p<0.0001) and Task 2 (p=0.0015). Combined feedback correlated with significantly lower energy expenditure compared to visual feedback in Task 1 (p<0.0001) and Task 3 (p=0.0003). Likewise, haptic feedback was associated with significantly lower energy expenditure compared to the visual feedback in Task 1 (p<0.0001), Task 2 (p<0.0001) and Task 3 (p<0.0001). These results suggest that mechanotactile feedback provided by the haptic sleeve effectively augments grasping and reduces its energy expenditure.